2003
DOI: 10.1023/a:1024767805397
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Two types of neurons exhibiting various reactions to application of antibodies against S100 protein in the washing solution were revealed in the nervous system of Helix lucorum snails. After treatment with antibodies against S100 protein the frequency of action potential generation decreased in spontaneously active B1, B3, B17, and PPa6 cells, but increased in B4 and B6 cells. The effect of antibodies against S100 was less pronounced in the solution of potentiated antibodies against this protein. After pre-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Thus, it was shown that RAF of Abs to S100 has similar effects as the S100 protein; direct action on membrane stabilization could modify S100 protein activity, and its effect has tight connections with membrane structures. 12 , 14 16 , 49 Based on these observed effects, it could be assumed that RAF of Abs to S100 alters receptor binding and signaling through regulation of S100 cellular activities. S100 proteins regulate a diverse array of cellular activities, including membrane–cytoskeleton interactions, cytoskeleton dynamics, 19 and membrane rearrangement, 20 could affect the organization of lipid domains (rafts), 50 and effect the modulation of the receptors function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it was shown that RAF of Abs to S100 has similar effects as the S100 protein; direct action on membrane stabilization could modify S100 protein activity, and its effect has tight connections with membrane structures. 12 , 14 16 , 49 Based on these observed effects, it could be assumed that RAF of Abs to S100 alters receptor binding and signaling through regulation of S100 cellular activities. S100 proteins regulate a diverse array of cellular activities, including membrane–cytoskeleton interactions, cytoskeleton dynamics, 19 and membrane rearrangement, 20 could affect the organization of lipid domains (rafts), 50 and effect the modulation of the receptors function.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the neuroprotective effect of low doses NMDA was shown to be mediated by activation of synaptic and extrasynaptic NMDA receptors fi nally increasing neuronal excitability [12]. The protective effect of low doses of antibodies to Са 2+ -binding protein S100 manifests in modulation of the effects of the main S100-Ab solution on specifi c neuronal structures, particularly on channels of inward and outward current (primary Са 2+ -channels), but not only in modulation of the membrane and threshold potentials and duration of action potential, which emphasizes the genesis of the main phenomenon and points to the location of its mechanism at the level of ion channels, which participate in action potential generation and provide calcium ion infl ux to the cell [1].…”
Section: Resultsmentioning
confidence: 99%
“…Interesting results were obtained when basic substance was administered in combination with diluted form (low doses) [8]. Recent experiments on isolated preparation of He lix lucorum nervous system revealed two types of neurons responding by different ways to application of antibodies to Са-binding protein S100 (AB-S100): the frequency of action potentials decreased in B1 and B17 neurons and increased in neurons B4 and B6 [1,8]. It was found that these changes in the main properties of the neuronal membrane induced by AB-S100 in physiological doses can be prevented by preincubation (preconditioning) of these "simple systems" with the same antibodies in low doses (dilution 10 -12 ).…”
mentioning
confidence: 99%
“…The preparation of CNS included the complex of subesophageal ganglia. Before the study all animals were cooled in ice-cold water for 20-30 min [1]. The measurements were performed at 20-22 o C using intracellular glass microelectrodes (resistance 5-40 MΩ) filled with 2.5 M KCl.…”
Section: Methodsmentioning
confidence: 99%
“…Experiments on isolated nervous system of Helix lucorum identified two types of neurons demonstrating different reaction to AB-S100 application: the frequency of AP generation decreased in B1 and B17 neurons, but increased in B4 and B6 neurons [1,7]. The main properties of the neuronal membrane and synaptic structures do not decrease when nervous tissue preparations are preincubated with low doses of AB-S100 (10 -12 M, LAB-S100) prior to AB-S100 treatment (so-called protective phenomenon).…”
mentioning
confidence: 99%